RETORIKA SEBAGAI ILMU KOMUNIKASI DALAM BERDAKWAH - Asriadi Asriadi (Al-MUNZIR, 2020)
Rhetoric is a game, processing or language style that we use in delivering a message in the form of speeches, lectures and others to mad`u. Speaking or giving speeches in public places there are several things that must be noticed by the communicant in order to know, so that they must be able and able to master the "rhetoric" both formally, informally as well as technically for effective communication. Because what is expected from the results of communication is how the audience can respond to what the contents of the speech material presented by the communicant. Where minimal rhetoric has ethos, phatos, and logos. Communicating the message of the communicator should design the message in such a way that it can attract the attention of the audience, the message should be able to reveal the cues of the same experience with the audience so that they are easy to understand, and the message should be able to offer a way that is relevant to the overall situation where all groups of audiences are stranded.